How Teachers Connect Elementary School Science Material with Students' Local Papuan Experiences: Cara Guru Menghubungkan Materi Sains Sekolah Dasar Dengan Pengalaman Lokal Kepapuaan Yang dimiliki Oleh Siswa - Hanida, Zurruyah Nur; Husna, Riska Latifatul (SEARCH: Science Education Research Journal, 2023)
This research seeks to describe information about how teachers connect elementary school science material with students' local Papuan experiences. The type of research used was descriptive qualitative with data sources namely 7 class teachers in various elementary schools in Papua. The data collection method in this research is through interviews. Meanwhile, data analysis techniques go through the stages of data presentation and data verification. The results of the research show that in connecting science material with students' local Papuan experiences, the teacher invites students directly to observe the process of chopping sago and then relates this to the material. Apart from that, teachers teach science material related to students' local Papuan experiences such as natural resources in Papua and the daily lives of Papuan people who depend on nature